Pengaruh Stres Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan PT Famed Calibration - Hayu Rohmawati; Siska Maya; Hamzah Robbani (Neolectura, 2020)
Employee performance is a description of the level of achievement of the implementation of a program of activities or policies in realizing the goals, objectives, vision and mission of the organization which is expressed through the strategic planning of an organization. The purposes of this study are: 1) to determine whether there is an influence between job stress and job satisfaction on the performance of employees of PT Famed Calibration, 2) to find out whether there is an effect of work stress on employee performance at PT Famed Calibration, 3) to determine whether there is an effect of job satisfaction on the performance of employees of PT Famed Calibration. The type of research used in this research is quantitative research with an associative research approach. The sample used purposive sampling method, namely by directly selecting all employees as many as 70 people. The data collection method used is a questionnaire. The data were analyzed by multiple linear regression with the help of SPSS 19 software for windows. The study found that all hypotheses in this study have been proven. 1) Job stress and job satisfaction have a simultaneous effect on employee performance at the PT Famed Calibration, 2) Job satisfaction has a partial effect on employee performance at PT Famed Calibration, 3) Job stress partially affects the performance of PT Famed Calibration